Mesenchymal Stem Cell-Derived Exosomes: Hope for Spinal Cord Injury Repair - Ren, Zhihua; Qi, Yao; Sun, Siyuan; Tao, Yuanyuan; Shi, Riyi (Stem cells and development, 2020)
Spinal cord injury (SCI) is a devastating medical condition with profound social and economic impacts. Although research is ongoing, current treatment options are limited and do little to restore functionality. However, recent studies suggest that mesenchymal stem cell-derived exosomes (MSC-exosomes) may hold the key to exciting new treatment options for SCI patients. MSCs are self-renewing multipotent stem cells with multi-directional differentiation and can secrete a large number of exosomes (vesicles secreted into the extracellular environment through endocytosis, called MSC-exosomes). These MSC-exosomes play a critical role in repairing SCI through promoting angiogenesis and axonal growth, regulating inflammation and the immune response, inhibiting apoptosis, and maintaining the integrity of the blood-spinal cord barrier. Furthermore, they can be utilized to transport genetic material or drugs to target cells, and their relatively small size makes them able to permeate the blood-brain barrier. In this review, we summarize recent advances in MSC-exosome themed SCI treatments and cell-free therapies to better understand this newly emerging methodology.